North Sea oil in the future Economic analysis and government policy - Robinson, Colin 1932-; Morgan, Jon (Macmillan, 1978)
Written for the Trade Policy Research Centre in London. Gives a detailed and independent analysis of the economics of North Sea oil.
Keywords: Politique énergétique - Grande-Bretagne; Politique énergétique - Norvège; Política energética - Europa; Pétrole - Industrie et commerce - Grande-Bretagne; Pétrole - Industrie et commerce - Norvège; Pétrole offshore - Industrie - Noire, Mer; Petroleum in submerged lands -- North Sea; Petroleum industry and trade -- Great Britain; Petroleum industry and trade -- North Sea; Erdöl; Wirtschaftspolitik; Erdöllagerstätte; Großbritannien; Nordsee